2017
DOI: 10.1111/dar.12510
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric review of drug and alcohol research focused on Indigenous peoples of Australia, New Zealand, Canada and the United States

Abstract: The dominance of descriptive research in the Indigenous drug and alcohol field is less than optimal for generating evidence to inform Indigenous drug and alcohol policy and programs. [Clifford A, Shakeshaft A. A bibliometric review of drug and alcohol research focused on Indigenous peoples of Australia, New Zealand, Canada and the United States. Drug Alcohol Rev 2017;36:509-522].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…Only 13 peerreviewed studies across a 21-year search period were identified. The relatively small number of dissemination studies is consistent with that of previous reviews of dissemination research in the Indigenous health field [15,33]. This indicates that, as with dissemination research in the Indigenous health field generally, the development of dissemination research in the Indigenous alcohol field is progressing slowly.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Only 13 peerreviewed studies across a 21-year search period were identified. The relatively small number of dissemination studies is consistent with that of previous reviews of dissemination research in the Indigenous health field [15,33]. This indicates that, as with dissemination research in the Indigenous health field generally, the development of dissemination research in the Indigenous alcohol field is progressing slowly.…”
Section: Discussionsupporting
confidence: 82%
“…Encouragingly, all three evaluation studies were rated methodologically adequate. No evaluation studies however employed randomisation or a control group, a finding consistent with a recent review of drug and alcohol interventions targeting Indigenous Australian peoples [33]. There was limited standardisation evident in the included evaluation approaches, but data sets were triangulated well and qualitative data were often used to strengthen the validity of conclusions.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations